Strategi Guru Kelas Meningkatkan Keterampilan Literasi Kelas II pada Madrasah Ibtidaiyah Negeri 2 Sambas - Dina Uswatun Hasanah; Ubabuddin; Wulan Purnamasari (Jurnal Pendidikan Dasar Islam, 2023)
The aim of this research is to find out and analyze class teacher strategies to improve reading literacy skills, namely by teaching students to understand reading texts and pay attention to each word. Basically, students are taught during PAUD/TK. But in reality there are still students who cannot recognize letters or read, write and count. This research method uses qualitative phenomenological research. The data source used is the MIN 2 Sambas teacher. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data display and data conclusions. The results of the research show that the class teacher's strategy improves reading literacy skills, namely by teaching students to understand the reading text and pay attention to each word in the reading, and repeating the reading as often as possible. reading in the library. The methods taught to teach students are: a). alphabet method, for example recognizing the letters a b c. b). spelling method, example of spelling letters, c). syllable method for example ba, ca, da and so on. d). method example words run, like and so on. e). The SAS method is to display or introduce a complete sentence